Teaching Practices and Learning outcomes in India - Singh , Narendra (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Effective teacher learning and professional development is important for student achievement. Teacher learning is a continuous process that promotes teachers' teaching skills, master new knowledge, develop new proficiency, which in turn, help improve students' learning. Modern society demands high quality teaching and learning from teachers. Teachers must possess a great deal of knowledge and skills regarding both teaching and assessment practices to meet those demands and standards of quality education. Classroom management influence student learning environment and student learning outcome. A growing body of research in classrooms has demonstrated that teachers do make a tangible difference in student achievement, high quality teacher learning influences student-learning outcome as a result. Teachers must undergo cognitive and metacognitive learning processes to achieve learning outcome in the form of changed believes about their practice or, even better, change in behaviour. These processes are cognitive thinking activities that are used to process learning content, for example classroom management. Teacher outcomes in terms of improved knowledge and skills in a field of classroom management influence student learning environment and student learning outcome because of changed student learning processes. Teachers should concentrate on emotional support, classroom organization and instructional support aspects of classroom interaction among teacher and students. To be able to do that, it requires that the teacher, possesses a certain set of knowledge and skills to understand how these three domains work, what difference they can make for a teacher in the classroom and why they are so important. This paper will access the Teachers instructional practices and process system and its impact on learning outcome. These are all such methods that tell our students to enhance their learning outcome or take them away. In the 21st Century we have to say that these methods have a great need today